Professional development activities of English language lecturers in Vietnam through the lens of sociocultural theory (Journal of Applied Learning and Teaching, 2024)
Sociocultural theory emphasizes that social interaction and interaction with cultural artifacts lead to development. Adopting these principles of sociocultural theory, the current study aims to investigate the implementation of professional development activities for 56 English language lecturers at a tertiary institution in Vietnam and how these activities mediated their teaching careers. All of the lecturers were invited to participate in a survey, and 20 of them were interviewed. The findings indicate that for professional development, the English language lecturers considered interaction through students’ feedback or course evaluation the most common activity, followed by interaction with colleagues via workshops, seminars, and conferences at different levels. In addition, the lecturers used videos, webinars, websites, books, and databases to create resources for their teaching. The mediating roles of social interaction, self-regulation, and artifacts were found to impact teachers’ cognitive aspects, including knowledge, teaching skills, research, and also their enhanced motivation to work. From the findings, recommendations are put forward for the availability of regular training activities, opportunities for teachers to socialize, and the abundance of cultural and digital resources as affordances for teachers’ professional development.